INFLUÊNCIA DA APLICAÇÃO DE SUBDOSES DE 2,4-D NO CRESCIMENTO E DESENVOLVIMENTO DO SISTEMA RADICULAR DO ALGODOEIRO - ALMEIDA, Rafael Lopes de; GOMES, Paulo Antônio Maciel; ZOZ, Tiago; BARBOSA, Willams Ferreira Souza; CHAGAS, Paulo Henrique Menezes; ZOZ, André (ANAIS DO ENIC, 2017)
-